The structural stability of monomeric glucose-6-phosphate dehydrogenase and its relationship to G6PD deficiency - Nguyen, Nhung T. T.; Le, Hoang Phong; Nguyen, Thi Hai Yen; Bui, Phuong Thuy; Mai, Thi Lan; Trinh, Xuan Hoang (Communications in Physics, 2026)
G6PD deficiency, an enzymopathy associated with glucose-6-phosphate dehydrogenase (G6PD), is caused by genetic mutations that reduce the enzyme activity, resulting in hemolytic anemia. Biochemical studies have shown that G6PD deficiency in various variants is associated with reduced thermal stability, reduced catalytic activity, or both. In this study, we investigate thestructural stability of the wild-type G6PD monomer at a physiological temperature using molecular dynamics simulations, in the absence and in the presence of its G6P and NADP+ ligands. We find that the G6P ligand has a low affinity for the G6PD monomer, which may result from fluctuations in the size of its binding pocket. This finding is consistent with and helps explain the catalyticinactivity of monomeric G6PD. Our analysis also shows that, with a statistically significant confidence, class I mutations occur preferentially at residues that are more flexible than randomly selected residues, whereas class II mutations tend to occur at residues that are less flexible than randomly selected ones. This result reflects the distinct structural roles of the G6PD mutation sites and further supports the relationship between enzyme activity and thermal stability.